Optimal Control of Stochastic Dynamic Systems of a Random Structure with Poisson Switches and Markov Switching - Svitlana V. Antonyuk; Marian F. Byrka; Mykola Y. Gorbatenko; Taras O. Lukashiv; Igor V. Malyk (Journal of Mathematics)
The problem of synthesis of the optimal control for a stochastic dynamic system of a random structure with Poisson perturbations and Markov switching is solved. To determine the corresponding functions for Bellman functional and optimal control the system of ordinary differential equation is investigated.